PELATIHAN STRATEGI KOMUNIKASI PEMASARAN DALAM MEMBANGUN BRAND IMAGE KLUB BULUTANGKIS FORTUNA GRESIK - Hanik, Siti Umi; Ivana, Wahyu; Nur’Aini, Dewi Ayu; Elisatussya’bania; Zulinar, Ariel Teta; Anggraini, Pipit Dwi; Wardhana, Rifqi Wahyu (UNIVERSITAS SERAMBI MEKKAH, 2024)
Marketing Communication Strategy Training in Building the Brand Image of the Fortuna Gresik Badminton Club. This activity was carried out to improve the potential and competence of the teachers and the Fortuna Gresik badminton club team in building a brand image as a professional club. Lecturers and students of the University of Gresik succeeded in providing marketing strategy training that was carried out so that coaches, and staff were able to build the brand image of the badminton club. In building the brand image of the Fortuna Gresik club, an integrated marketing communication strategy was used, including Interactive, Direct Marketing, Public Relations, Personal Selling and Advertising. From the use of an integrated marketing communication strategy, the badminton club was able to build a professional brand image well so that it attracted the people of Gresik.